An injectable collagen composite hydrogel and its preparation method and application

The polymethyl methacrylate-polylactic acid core-shell microspheres prepared by membrane emulsification combine with collagen and oxidized sodium alginate to form an injectable collagen-complex hydrogel, which solves the immediate and long-term shaping problems of hydrogels in the field of biomedical medicine, achieves continuous supplementation and degradation of collagen, and reduces the occurrence of adverse reactions.

CN119075004BActive Publication Date: 2025-04-18清泽医疗科技(广东)有限公司
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202410998212.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-24
Publication Date
2025-04-18
Estimated Expiration
2044-07-24

AI Technical Summary

Technical Problem

The prior art is difficult to achieve immediate and long-term shaping of injectable hydrogels in the field of biomedical use, and the degradation of collagen is relatively fast, which may lead to adverse reactions.

Method used

Polymethyl methacrylate-polylactic acid core-shell microspheres were prepared by membrane emulsification method, and combined with collagen and oxidized sodium alginate to form an injectable collagen-complex hydrogel.

Benefits of technology

The instant filling effect and long-term shaping of the hydrogel are achieved, the degradation rate of collagen is reduced, the occurrence of adverse reactions is reduced, and local labor pain is relieved through sustained release drugs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119075004B_ABST
    Figure CN119075004B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of biomedical materials, and specifically relates to an injectable collagen composite hydrogel and its preparation method and application. The preparation method of the above-mentioned injectable collagen composite hydrogel is as follows: using polymethyl methacrylate solution and / or polyvinyl alcohol solution as the aqueous phase and polylactic acid solution as the oil phase, a membrane emulsification method is used to prepare polymethyl methacrylate-polylactic acid core-shell microspheres; the polymethyl methacrylate-polylactic acid core-shell microspheres are added to the collagen solution to obtain a mixed solution; and oxidized sodium alginate is added to the mixed solution to obtain the injectable collagen composite hydrogel. The present invention can increase the viscosity of the microsphere carrier and increase the immediate shaping effect after the gel is injected; the polymethyl methacrylate-polylactic acid core-shell microspheres prepared by the membrane emulsification method can load and release drugs while continuously and effectively stimulating collagen regeneration and exerting a long-lasting filling effect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of biomedical materials, and in particular relates to an injectable collagen composite hydrogel and a preparation method and application thereof. Background Art

[0002] Injectable hydrogel refers to a type of hydrogel that has a certain fluidity and can be applied by injection. Injectable hydrogels may show a mutual transformation between sol and gel in response to external stimuli (temperature, pH, etc.). Compared with traditional hydrogels, injectable hydrogels have the advantage of minimally invasive applications. It not only expands the application scope of hydrogels in the biomedical field, including drug and cell delivery, soft tissue repair, regenerative medical filling, etc., but also improves the comfort and satisfaction of patients, and to a certain extent reduces the application cost.

[0003] Collagen is the main component of human ECM, providing physical support for tissues and organs, and has good tensile strength and elasticity. Collagen can interact with a large number of macromolecules, such as integrins, decorative proteins, fibronectin, heparin, metalloproteinases (MMPs), etc., to regulate tissue regeneration. Aging is often accompanied by the loss, reorganization and breakage of collagen. The breakage of collagen will damage its interaction with fibroblasts, change the adhesion morphology of cells, and reduce the mechanical properties of the extracellular matrix. Therefore, collagen can supplement the missing collagen and maintain the healthy state of the ECM environment. However, when collagen is used for filling, it can not maintain the fullness of the skin for a long time, that is, the degradation rate of collagen in the body is relatively fast. The toxicity produced by direct cross-linking with chemical cross-linking agents may aggravate more adverse reactions in the skin after implantation.

[0004] Sodium alginate is a byproduct of extracting iodine and mannitol from brown algae such as kelp or sargassum. Its molecule is composed of β-D-mannuronic acid (β-D-mannuronic, M) and α-L-guluronic acid (α-L-guluronic, G) connected by (1→4) bonds. It is a natural polysaccharide with the stability, solubility, viscosity and safety required for pharmaceutical excipients. It has good biocompatibility and lacks specific degrading enzymes in the human body, so it can exist safely in the body for a long time. Sodium alginate can be made into a degradable material after sodium periodate peroxidation for implantation or interventional treatment. Cross-linking oxidized sodium alginate with collagen can reduce the degradation rate of collagen.

[0005] Both polymethyl methacrylate and polylactic acid can be made into microspheres through emulsification reaction, and these microspheres have been successfully used in the field of medical beauty injection. Among them, the microspheres prepared by polymethyl methacrylate are a non-absorbable material with excellent biocompatibility, light transmittance and inertness. The microspheres prepared by polylactic acid can be gradually degraded into carbon dioxide and water. After a few months of injection, the polylactic acid microspheres will begin to degrade, and their effective support time is 1 to 2 years. After polymethyl methacrylate and polylactic acid are prepared into core-shell microspheres, the skin shaping time can be effectively prolonged, while reducing the adverse reactions of the skin due to foreign bodies. At the same time, suitable microsphere carriers are the key to maintaining skin moisture and have an immediate shaping effect. Furthermore, how to achieve immediate shaping and long-term shaping without causing obvious inflammatory reactions is a problem that the existing technology needs to solve. Summary of the invention

[0006] In order to overcome the shortcomings of the prior art, one of the purposes of the present invention is to provide a method for preparing an injectable collagen composite hydrogel to solve the technical problem that the hydrogel in the prior art cannot achieve immediate shaping and long-term shaping.

[0007] One of the purposes of the present invention is achieved by the following technical solution:

[0008] A method for preparing an injectable collagen composite hydrogel comprises the following steps:

[0009] (1) using polymethyl methacrylate solution and / or polyvinyl alcohol solution as the aqueous phase and polylactic acid solution as the oil phase, and preparing polymethyl methacrylate-polylactic acid core-shell microspheres by membrane emulsification method;

[0010] (2) adding the polymethyl methacrylate-polylactic acid core-shell microspheres into a collagen solution to obtain a mixed solution; and then adding oxidized sodium alginate into the mixed solution to obtain the injectable collagen composite hydrogel.

[0011] Furthermore, the membrane emulsification method in step (1) comprises the following steps: mixing a polymethyl methacrylate solution and a polyvinyl alcohol solution to obtain an aqueous phase 1, and using the polyvinyl alcohol solution as an aqueous phase 2; pressing the aqueous phase 1 through a hydrophobic membrane into an oil phase to obtain a microsphere mixture; then pressing the microsphere mixture through a hydrophilic membrane into the aqueous phase 2 to obtain a mixture; and removing the polyvinyl alcohol in the mixture to obtain the polymethyl methacrylate-polylactic acid core-shell microspheres.

[0012] Furthermore, the hydrophobic membrane is a hydrophobic polytetrafluoroethylene membrane with holes having a pore size of 20 to 30 μm, and the hydrophilic membrane is a hydrophilic polytetrafluoroethylene membrane with holes having a pore size of 30 to 40 μm.

[0013] Furthermore, the concentration of the polymethyl methacrylate solution is 5% to 15wt%, the concentration of the polyvinyl alcohol solution is 1% to 10wt%; and the concentration of the polylactic acid solution is 5% to 15wt%.

[0014] Furthermore, based on the total mass of the injectable collagen composite hydrogel, the mass of polymethyl methacrylate-polylactic acid core-shell microspheres accounts for 10-30% of the total mass, and the sum of the mass of collagen and oxidized sodium alginate accounts for 70-90% of the total mass;

[0015] Furthermore, the mass ratio of the collagen to oxidized sodium alginate is 4 to 19:1.

[0016] Furthermore, the water phase 1 or the water phase 2 also contains an oil-in-water emulsifier, and the oil phase also contains an oil-in-water emulsifier; the oil-in-water emulsifier is at least one of Tween 20, Tween 40, and Tween 60; the oil-in-water emulsifier is at least one of Span 80, Span 60, and Span 40.

[0017] Furthermore, the added amount of Tween 20 is 0.3wt% of the water phase 1 or the water phase 2, and the added amount of Span 80 is 0.3wt% of the oil phase.

[0018] Furthermore, the preparation method of oxidized sodium alginate includes the following steps: mixing a sodium alginate solution with a concentration of 1 to 10 wt% and a sodium periodate solution with a concentration of 0.1 to 5 wt%, stirring for 24 hours at room temperature in the dark to obtain a reaction solution, adding a 0.5 to 5 wt% ethylene glycol solution and a 0.5 to 5 wt% sodium chloride solution to the reaction solution, continuing to stir for 0.5 to 2 hours, stopping stirring, and then ultrafiltration to obtain an oxidized sodium alginate stock solution.

[0019] Furthermore, the water-in-oil emulsifier is Tween 20; the oil-in-water emulsifier is Span 80.

[0020] Furthermore, the solvent of the polymethyl methacrylate solution is dichloromethane, the solvent of the polyvinyl alcohol solution is water, and the solvent of the polylactic acid solution is dichloromethane.

[0021] Furthermore, the concentration of the collagen solution is 3-5wt%.

[0022] A second object of the present invention is to provide an injectable collagen composite hydrogel.

[0023] The second object of the present invention is achieved by adopting the following technical solution:

[0024] The injectable collagen composite hydrogel was prepared by the above method.

[0025] The third object of the present invention is to provide an application of an injectable collagen composite hydrogel.

[0026] The third object of the present invention is achieved by adopting the following technical solution:

[0027] Application of the above-mentioned injectable collagen composite hydrogel in the field of medical materials.

[0028] Furthermore, the above-mentioned injectable collagen composite hydrogel is used in the field of plastic surgery materials.

[0029] The uniformity of the particle size of the microspheres implanted in the body needs to be effectively controlled. The reason is that the microspheres are too small and have obvious defects. For example, if the microsphere size is less than 20 μm, it is easy to be phagocytosed by macrophages, easy to enter the gaps between deep dermal fibers, and even promote lymphocyte infiltration and angiogenesis. If the microsphere size is too large, it is easy to cause a more serious inflammatory reaction. In addition, as the size gradually decreases, the specific surface area of ​​the microspheres will increase significantly, which can promote the production of collagen (for example, a microsphere size of 100 μm can promote the growth of 56% of related connective tissue; and a microsphere of 40 μm can promote the growth of 80% of associated connective tissue). At the same time, it can cleverly avoid the significant performance defects that may be caused by too small a size. Therefore, the present invention controls the particle size of the microspheres to 20 to 40 μm.

[0030] The polymethyl methacrylate-polylactic acid core-shell microspheres prepared by the present invention can uniformly control the particle size of the microspheres by membrane emulsification, wherein Tween 20 is an oil-in-water emulsifier and Span 80 is an oil-in-water emulsifier. The first layer of hydrophobic polytetrafluoroethylene membrane mainly controls the particle size of the core layer polymethyl methacrylate microspheres to be 20 to 30 μm, and the second layer of hydrophilic biaxially stretched polytetrafluoroethylene membrane mainly controls the thickness of the shell layer polylactic acid to be about 10 μm. At the same time, as the core-shell microspheres are implanted in the body, the shell layer polylactic acid will slowly degrade, while the core layer polymethyl methacrylate can retain the effect of continuous shaping.

[0031] As a filler, collagen has the advantages of moisturizing, firming, wrinkle-reducing, repairing and restoring skin elasticity, but its disadvantage is that it can only maintain skin shaping for a short time, only 3 to 6 months, and the triple helix structure of collagen may also produce immune reactions. The addition of oxidized sodium alginate can form an interpenetrating network structure with collagen, locking in moisture to a greater extent, thereby increasing the dynamic viscosity and swelling degree of the sample, and better achieving an instant filling effect.

[0032] Compared with the prior art, the present invention has the following beneficial effects:

[0033] (1) The microspheres prepared by the membrane emulsification method of the present invention have more uniform microsphere particle size; after collagen and oxidized sodium alginate are cross-linked, the viscosity of the microsphere carrier can be increased, thereby increasing the immediate shaping effect after gel injection.

[0034] (2) The present invention prepares polymethyl methacrylate-polylactic acid core-shell microspheres by an emulsification method, which can load lidocaine hydrochloride to achieve sustained release of lidocaine hydrochloride and alleviate the local pain caused by product implantation. At the same time, polymethyl methacrylate-polylactic acid core-shell microspheres can continuously and effectively stimulate collagen regeneration and continue to exert a long-term filling effect. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 It is a schematic diagram comparing the effects of Example 1 of the present invention and Comparative Example 3 on collagen. DETAILED DESCRIPTION

[0036] Below, in conjunction with the accompanying drawings and specific embodiments, the present invention is further described. It should be noted that, under the premise of no conflict, the embodiments described below or the technical features can be arbitrarily combined to form new embodiments. The specific conditions not specified in the embodiments are carried out according to conventional conditions or conditions recommended by the manufacturer. The reagents or instruments used, unless otherwise specified, are conventional products obtained through commercial channels.

[0037] The preparation method of the collagen solution in the following embodiments of the present invention is as follows:

[0038] The method comprises the following steps: purchasing bovine Achilles tendon (or pig skin, rat tail tendon), removing fat, inactivating, cleaning, crushing and drying the tendon, and then immersing the tendon in 0.05-0.5 mol / L acetic acid to swell the tendon, adding pepsin and stirring the tendon for 48 hours to obtain a mixed solution; then centrifuging the mixed solution in a refrigerated centrifuge at 4°C at 5000-15000 rad / min for 10-20 minutes, collecting the supernatant; adding 2-3 mol / L sodium chloride solution to the supernatant, stirring the tendon for 4-8 hours, and standing the tendon overnight to precipitate collagen; purifying the collagen with a 100KDa ultrafiltration membrane to obtain a collagen stock solution; and freeze-drying the collagen in a low-temperature vacuum freeze drying oven for 48 hours to obtain purified freeze-dried collagen; and re-dissolving the freeze-dried collagen with an acetic acid solution having a concentration of 0.05-0.5 mol / L to obtain a collagen solution, wherein the concentration of the collagen solution is 3-5 wt%.

[0039] Example 1

[0040] A method for preparing an injectable collagen composite hydrogel comprises the following steps:

[0041] (1) dissolving polymethyl methacrylate in dichloromethane to obtain a 10 wt % polymethyl methacrylate solution; heating polyvinyl alcohol and dissolving it in purified water to obtain a 1 wt % polyvinyl alcohol solution; dissolving polylactic acid in dichloromethane to obtain a 10 wt % polylactic acid solution for later use;

[0042] (2) 10 wt% polymethyl methacrylate solution, 1 wt% polyvinyl alcohol solution and Tween 20 are mixed to form an emulsion to obtain an aqueous phase 1, wherein Tween 20 accounts for 0.3 wt% of the aqueous phase 1, and the volume ratio of the polymethyl methacrylate solution to the polyvinyl alcohol solution is 1:1; 10 wt% polylactic acid solution and Span 80 are mixed to form an emulsion to obtain an oil phase, wherein Span 80 accounts for 0.3 wt% of the oil phase; 1 wt% polyvinyl alcohol solution and Tween 20 are mixed to form an emulsion to obtain an aqueous phase 2, wherein Tween 20 accounts for 0.3 wt% of the aqueous phase 2;

[0043] (3) passing the aqueous phase 1 through a porous hydrophobic polytetrafluoroethylene membrane (pore size of 25 μm) and pressing it into the oil phase to obtain a microsphere mixture; then passing the microsphere mixture through a porous hydrophilic biaxially stretched polytetrafluoroethylene membrane (pore size of 35 μm) and pressing it into the aqueous phase 2 to obtain a mixture; centrifuging the mixture at 8000 rad / min to remove polyvinyl alcohol, and freeze-drying the mixture for 48 hours to obtain polymethyl methacrylate-polyvinyl alcohol core-shell microspheres;

[0044] (4) adding polymethyl methacrylate-polyvinyl alcohol core-shell microspheres to the above 3 wt % collagen solution to obtain a collagen solution of core-shell microspheres;

[0045] (5) Mix 5wt% sodium alginate solution and 2wt% sodium periodate solution, stir in the dark at room temperature for 24h, then add 2wt% ethylene glycol solution and 2wt% sodium chloride solution, wherein the molar ratio of ethylene glycol to sodium periodate is 1:1, continue stirring for 2h and terminate the reaction; purify the reaction solution with a 1KDa ultrafiltration membrane to obtain an oxidized sodium alginate stock solution, and then freeze-dry it in a low-temperature vacuum freeze drying oven for 48h to obtain purified oxidized sodium alginate; take a certain amount of oxidized sodium alginate and dissolve it in purified water, add it to the collagen solution of core-shell microspheres, and obtain an injectable collagen composite hydrogel. Among them, the mass ratio of collagen to oxidized sodium alginate is 19:1; the polymethyl methacrylate-polylactic acid core-shell microspheres in the injectable collagen composite hydrogel are 20wt%, and the collagen and oxidized sodium alginate gel content is 80%.

[0046] Example 2

[0047] A method for preparing an injectable collagen composite hydrogel is basically the same as that of Example 1, except that: in step (3), the pore size of the hydrophobic polytetrafluoroethylene membrane is 20 μm, and the pore size of the hydrophilic biaxially stretched polytetrafluoroethylene membrane is 30 μm; in step (5), the mass ratio of collagen to oxidized sodium alginate is 9:1; in the injectable collagen composite hydrogel, the content of polymethyl methacrylate-polylactic acid core-shell microspheres is 10wt%, and the content of collagen and oxidized sodium alginate gel is 90%.

[0048] Example 3

[0049] A method for preparing an injectable collagen composite hydrogel is basically the same as that of Example 1, except that: in step (1), the concentration of polymethyl methacrylate is 5wt%, the concentration of polyvinyl alcohol is 10wt%, and the concentration of polylactic acid is 15wt%; in step (3), the pore size of the hydrophobic polytetrafluoroethylene membrane is 30μm, the pore size of the hydrophilic biaxially stretched polytetrafluoroethylene membrane is 40μm, the polyvinyl alcohol is removed by centrifugation at 15000rad / min, and freeze-dried for 24h; in step (5), the concentration of the sodium alginate solution is 1wt%, the concentration of the sodium periodate solution is 0.1wt%, the concentration of the ethylene glycol solution is 0.5wt%, the concentration of the sodium chloride solution is 0.5wt%, the mass ratio of collagen to oxidized sodium alginate is 17:3, the content of polymethyl methacrylate-polylactic acid core-shell microspheres in the injectable collagen composite hydrogel is 30wt%, and the content of collagen and oxidized sodium alginate gel is 70%.

[0050] Example 4

[0051] A method for preparing an injectable collagen composite hydrogel is basically the same as that of Example 1, except that: in step (1), the concentration of polymethyl methacrylate is 15wt%, the concentration of polyvinyl alcohol is 5wt%, and the concentration of polylactic acid is 5wt%; in step (3), the polyvinyl alcohol is removed by centrifugation at 10000rad / min and freeze-dried for 36h; in step (4), the concentration of the collagen solution is 5wt%; in step (5), the concentration of the sodium alginate solution is 10wt%, the concentration of the sodium periodate solution is 5wt%, the concentration of the ethylene glycol solution is 5wt%, and the concentration of the sodium chloride solution is 5wt%, and the mass ratio of collagen to oxidized sodium alginate is 4:1.

[0052] Example 5

[0053] A method for preparing an injectable collagen composite hydrogel loaded with lidocaine hydrochloride is basically the same as that of Example 1, except that lidocaine hydrochloride is also added to the oil phase in step (2) during the preparation process, and the amount of lidocaine hydrochloride added is 0.3% of the total mass of the oil phase.

[0054] Comparative Example 1

[0055] A collagen solution of core-shell microspheres, the preparation method of which is basically the same as that of Example 1, except that: step (5) is omitted, that is, after the polymethyl methacrylate-polylactic acid core-shell microspheres are mixed with the collagen solution in step (4), they are not cross-linked with oxidized sodium alginate to form a hydrogel, and the mass ratio of the collagen solution to the polymethyl methacrylate-polylactic acid core-shell microspheres in the collagen solution of the core-shell microspheres is 4:1.

[0056] Comparative Example 2

[0057] A polymethyl methacrylate and polylactic acid microsphere, the preparation steps of which are:

[0058] (1) dissolving polymethyl methacrylate in dichloromethane to obtain a 10 wt % polymethyl methacrylate solution; heating polyvinyl alcohol and dissolving it in purified water to obtain a 1 wt % polyvinyl alcohol solution; dissolving polylactic acid in dichloromethane to obtain a 10 wt % polylactic acid solution for later use;

[0059] (2) The polymethyl methacrylate solution, the polyvinyl alcohol solution and the polylactic acid solution are mixed in an equal volume ratio to form an emulsion; the obtained emulsion is then centrifuged at 8000 rad / min to remove the polyvinyl alcohol, and then freeze-dried for 48 hours to obtain polymethyl methacrylate and polylactic acid microspheres.

[0060] Comparative Example 3

[0061] A polylactic acid microsphere, the preparation steps of which are: first dissolving polylactic acid in dichloromethane to obtain a 10wt% polylactic acid solution; heating polyvinyl alcohol to dissolve in purified water to obtain a 1wt% polyvinyl alcohol solution; mixing the polylactic acid solution and the polyvinyl alcohol solution to form an emulsion; then centrifuging the obtained polylactic acid solution and the polyvinyl alcohol emulsion at 8000rad / min to remove the polyvinyl alcohol, and then freeze-drying for 48h to obtain polylactic acid microspheres. The polylactic acid microspheres are added to the above-mentioned 3wt% collagen solution to obtain a collagen solution of polylactic acid microspheres, wherein the mass ratio of the collagen solution to the polylactic acid microspheres is 4:1.

[0062] Comparative Example 4

[0063] The invention discloses a polylactic acid microsphere loaded with lidocaine hydrochloride. The preparation steps of the polylactic acid microsphere are as follows: first dissolving polylactic acid in dichloromethane to obtain a 10wt% polylactic acid solution; heating polyvinyl alcohol to dissolve in purified water, and then adding lidocaine hydrochloride to obtain a mixed solution containing 1wt% polyvinyl alcohol and 0.3wt% lidocaine hydrochloride; uniformly mixing the polylactic acid solution with a mixed solution of polyvinyl alcohol and lidocaine hydrochloride to form an emulsion; then centrifuging the obtained polylactic acid solution and the mixed emulsion of polyvinyl alcohol and lidocaine hydrochloride at 8000rad / min to remove the polyvinyl alcohol, and then freeze-drying for 48h to obtain the polylactic acid microsphere loaded with lidocaine hydrochloride.

[0064] Test Example 1

[0065] The samples of Examples 1 to 3 and Comparative Example 1 were subjected to viscosity tests, with reference to the third method in the viscosity determination method of Part 0633 of the 2020 edition of the Pharmacopoeia of the People's Republic of China, and the results are shown in Table 1.

[0066] Table 1

[0067] Composite hydrogel Example 1 Example 2 Example 3 Comparative Example 1 Dynamic viscosity (Pa·s) 11.85 18.42 27.26 4.51

[0068] It can be seen from Table 1 that, compared with the hydrogel loaded with only pure collagen in Comparative Example 1, the oxidized sodium alginate in Examples 1 to 3 increases the dynamic viscosity of the hydrogel and can better achieve an instant filling effect.

[0069] Test Example 2

[0070] The samples of Examples 1 to 3 and Comparative Example 1 were subjected to a swelling test, and the method was as follows: an equal amount of the samples of Examples 1 to 3 and Comparative Example 1 were freeze-dried and weighed as m1, the dried samples were added to purified water, and after removing excess water, the weight was weighed as m2, and the swelling degree Q of the sample was calculated, swelling degree Q = (m2-m1) / m1. The test results are shown in Table 2.

[0071] Table 2

[0072] Composite hydrogel Example 1 Example 2 Example 3 Comparative Example 1 Swelling degree Q 16.84 18.52 21.69 14.62

[0073] It can be seen from Table 2 that compared with the collagen solution loaded with core-shell microspheres in Comparative Example 1, the swelling degree of the hydrogels in Examples 1 to 3 is significantly improved. This is because the oxidized sodium alginate and collagen in Examples 1 to 3 form an interpenetrating network structure, which can lock in moisture to a greater extent, thereby improving the swelling degree of the sample and better achieving an instant filling effect.

[0074] Test Example 3

[0075] The polymethyl methacrylate-polylactic acid core-shell microspheres obtained in steps (3) of Examples 1 to 3 and the sample of Comparative Example 2 were subjected to microsphere particle size statistics, and the method was as follows: the polymethyl methacrylate-polylactic acid core-shell microspheres in Example 1 and the polymethyl methacrylate and polylactic acid microspheres in Comparative Example 2 were configured into aqueous solutions of a certain concentration, and added to the sample pool of a laser particle size distribution analyzer. When the shading rate reached the minimum concentration requirement of the instrument, the detection was started to obtain the particle size distribution of the microspheres. The detection results are shown in Table 3.

[0076] Table 3

[0077]

[0078] It can be seen from Table 3 that compared with the polymethyl methacrylate and polylactic acid microspheres prepared by simple mixing in Comparative Example 2, the polymethyl methacrylate-polylactic acid core-shell microspheres prepared by the membrane emulsification method have better particle size uniformity. This method does not require screening of microspheres of different particle sizes to achieve uniform particle size control.

[0079] Test Example 4

[0080] The samples prepared in Example 1 and Comparative Example 3 were subjected to animal Masson staining experiments. The experimental method was as follows: 2.0-2.5 kg of male New Zealand white rabbits (source: Guangdong Medical Animal Experiment Center) were taken, and after anesthesia with a 40 mg / kg·bw dose of sodium pentobarbital solution injected into the ears, the hair in the surgical area was shaved, and the exposed skin part was disinfected with 75% alcohol cotton balls. The rabbits were randomly divided into an experimental group (samples in Example 1) and a control group (samples in Comparative Example 3), and 6 points were injected subcutaneously in each rabbit, with 5 mL per point. The experimental rabbits were raised in cages at 25°C, and allowed to freely drink water and eat. The growth of the rabbits was observed. After one year of feeding, the rabbits were humanely killed, the injected implants were cut off with sufficient unaffected surrounding tissues, and the tissue samples taken out were processed according to the requirements of histological evaluation. After being embedded in paraffin and sliced, Masson staining was performed.

[0081] The comparative diagram of the effects of Example 1 and Comparative Example 3 on collagen is shown in Figure 1 The results show that the collagen fibers in the sample of Example 1 are denser, because the collagen protein delays its degradation in the body after cross-linking with oxidized sodium alginate, and the continuous supplementation of collagen protein can reduce the degradation of collagen protein in the body by matrix metalloenzymes; at the same time, after the polylactic acid in the shell layer is degraded, the polymethyl methacrylate microspheres in the core layer can still continue to stimulate the regeneration of collagen protein in the body, achieving a more lasting shaping effect.

[0082] Test Example 5

[0083] The samples in Example 5 and Comparative Example 4 were tested for drug release rate, and the method was as follows: the samples in Example 5 and Comparative Example 4 were placed in PBS buffer at 37° C., and after 1 month, 3 months, 6 months, 9 months, and 12 months, the content of lidocaine hydrochloride in the PBS buffer was detected by high performance liquid chromatography, and the drug release in each time period was calculated. The test results are shown in Table 4.

[0084] Table 4

[0085]

[0086] It can be seen from Table 4 that, compared with the polylactic acid microspheres loaded with lidocaine hydrochloride in Comparative Example 4, the polymethyl methacrylate-polylactic acid core-shell microspheres loaded with lidocaine hydrochloride in Example 5 have a better sustained-release effect on lidocaine hydrochloride.

[0087] The above-mentioned embodiments are only preferred embodiments of the present invention and cannot be used to limit the scope of protection of the present invention. Any non-substantial changes and substitutions made by technicians in this field on the basis of the present invention shall fall within the scope of protection required by the present invention.

Claims

1. A method for preparing an injectable collagen composite hydrogel, characterized in that: The following steps are involved: (1) Using polymethyl methacrylate solution and / or polyvinyl alcohol solution as the aqueous phase and polylactic acid solution as the oil phase, polymethyl methacrylate-polylactic acid core-shell microspheres are prepared by membrane emulsification method; (2) adding the polymethyl methacrylate-polylactic acid core-shell microspheres to a collagen solution to obtain a mixed solution; and then adding oxidized sodium alginate to the mixed solution to obtain the injectable collagen composite hydrogel; The membrane emulsification method in step (1) comprises the following steps: mixing a polymethyl methacrylate solution and a polyvinyl alcohol solution to obtain an aqueous phase 1, and using the polyvinyl alcohol solution as an aqueous phase 2; The aqueous phase 1 is pressed into the oil phase through a hydrophobic membrane to obtain a microsphere mixture; the microsphere mixture is then pressed into the aqueous phase 2 through a hydrophilic membrane to obtain a mixture; polyvinyl alcohol in the mixture is removed to obtain the polymethyl methacrylate-polylactic acid core-shell microspheres; The concentration of the polymethyl methacrylate solution is 5wt%-15wt%, the concentration of the polyvinyl alcohol solution is 1wt%-10wt%; and the concentration of the polylactic acid solution is 5wt%-15wt%.

2. The method for preparing the injectable collagen composite hydrogel according to claim 1, characterized in that: The hydrophobic membrane is a hydrophobic polytetrafluoroethylene membrane with holes having a pore size of 20 to 30 μm, and the hydrophilic membrane is a hydrophilic polytetrafluoroethylene membrane with holes having a pore size of 30 to 40 μm.

3. The method for preparing the injectable collagen composite hydrogel according to claim 1, characterized in that: Based on the total mass of the injectable collagen composite hydrogel, the mass of polymethyl methacrylate-polylactic acid core-shell microspheres accounts for 10-30% of the total mass, and the sum of the masses of collagen and oxidized sodium alginate accounts for 70-90% of the total mass.

4. The method for preparing the injectable collagen composite hydrogel according to claim 1, characterized in that: The mass ratio of the collagen to oxidized sodium alginate is 4-19:

1.

5. The method for preparing the injectable collagen composite hydrogel according to any one of claims 1 to 4, characterized in that: The water phase 1 or the water phase 2 also contains an oil-in-water emulsifier, and the oil phase also contains an oil-in-water emulsifier; the oil-in-water emulsifier is at least one of Tween 20, Tween 40, and Tween 60; the oil-in-water emulsifier is at least one of Span 80, Span 60, and Span 40.

6. The method for preparing the injectable collagen composite hydrogel according to claim 5, characterized in that: The added amount of Tween 20 is 0.3wt% of the water phase 1 or the water phase 2, and the added amount of Span 80 is 0.3wt% of the oil phase.

7. An injectable collagen composite hydrogel prepared by the method according to any one of claims 1 to 6.

8. Use of the injectable collagen composite hydrogel according to claim 7 in the preparation of medical materials.

Citation Information

Patent Citations

  • Injectable artificial dermis for promoting wound healing as well as preparation method and application of injectable artificial dermis

    CN114225118A

  • Injectable temperature-sensitive composite hydrogel and application thereof in preparation of shaping and / or repairing filling material

    CN116712609A

  • Polymer core-shell microsphere as well as preparation method and application thereof

    CN117797118A